The Roles of CircRNAs in Regulating Muscle Development of Livestock Animals - Yang, Zhenguo; He, Tianle; Chen, Qingyun (Frontiers in Cell and Developmental Biology, 2021)
The muscle growth and development of livestock animals is a complex, multistage process, which is regulated by many factors, especially the genes related to muscle development. In recent years, it has been reported frequently that circular RNAs (circRNAs) are involved widely in cell proliferation, cell differentiation, and body development (including muscle development). However, the research on circRNAs in muscle growth and development of livestock animals is still in its infancy. In this paper, we briefly introduce the discovery, classification, biogenesis, biological function, and degradation of circRNAs and focus on the molecular mechanism and mode of action of circRNAs as competitive endogenous RNAs in the muscle development of livestock and poultry. In addition, we also discuss the regulatory mechanism of circRNAs on muscle development in livestock in terms of transcription, translation, and mRNAs. The purpose of this article is to discuss the multiple regulatory roles of circRNAs in the process of muscle development in livestock, to provide new ideas for the development of a new co-expression regulation network, and to lay a foundation for enriching livestock breeding and improving livestock economic traits.